Assessment of the Land and Building Tax (PBB) Collection Mechanism in Makassar’s Regional Revenue Agency - Muhammad Khaedar Sahib; Muhammad Adil; Rifdah Septiani Faisal (Universitas Muhammadiyah Makassar, 2025)
This study aims to evaluate the Land and Building Tax (PBB) collection system implemented by the Makassar City Regional Revenue Agency and to determine whether the current billing mechanism functions effectively. The focus is on identifying efforts to resolve recurring issues such as taxpayer resistance to billing, undelivered Tax Payable Notification Letters (SPPT), and discrepancies in ownership data. Using a qualitative research method, the study applies data reduction, presentation, and conclusion-drawing techniques to analyze findings from field observations and interviews. Results indicate that the Makassar City Regional Revenue Agency uses the Official Assessment System, where the tax amount is determined by the authority and communicated through SPPT. However, challenges remain, including taxpayer non-compliance, delayed payments, and administrative obstacles related to ownership data. The tax realization in both 2022 and 2023 did not meet the set targets, showing a shortfall of approximately 22% each year, suggesting inefficiencies in collection and public awareness. To address these challenges, the agency has introduced online payment systems like the Pakinta application and engaged in active collection efforts such as issuing warning letters and conducting outreach campaigns. Nonetheless, these initiatives require further strengthening. The study recommends increasing the number of field officers and optimizing task distribution to improve billing performance and achieve revenue targets in future fiscal periods. Overall, while the tax collection infrastructure is structurally sound, implementation gaps hinder its full potential